Bruton's Tyrosine Kinase: A Potential Novel Target for Neurological Disorders - Das, D; Ghosh, A; Greco, D; Michaličková, D; Slanař, O (Physiological research, 2025)
Bruton's tyrosine kinase (BTK) is a crucial part of the B-cell receptor signaling pathway that has been extensively studied in various types of malignancies. Recent studies have extended our knowledge on its role in metabolism as well as neurological disorders. It may play an important role in the pathophysiology of neurological diseases, such as multiple sclerosis, Alzheimer's disease, brain injury, and several others. Activation of inflammasomes, mainly NLRP3, is one of the core mechanisms by which it promotes inflammation in the brain related to aging and diseases. In this paper, we provide an overview of the less explored roles of BTK in several brain diseases and discuss the potential of its inhibition to become a therapeutic target for neurological diseases.
Keywords: inflamasomy; signální transdukce; Signal Transduction; Inflammasomes; inhibitory proteinkinas; nemoci nervového systému; Nervous System Diseases; zvířata; Humans; Agammaglobulinaemia Tyrosine Kinase; Protein Kinase Inhibitors; proteinkinasa BTK; lidé; Animals